Odpowiedź:
1.
(√2x + 5)² > 2x² + 5
2x² + 10√2x + 25 > 2x² + 5
2x² - 2x² + 10√2x > 5 - 25
10√2x > - 20
x > - 20/10√2
x > - 20√2/(10 * 2)
x > - 20√2/20
x > - √2
2.
a)
1/√7 = 1/√7 * √7/√7 = √7/√7² = √7/7
b)
1/(2 - √3) = (2 + √3)/[(2 - √3)(2 + √3)] = (2 + √3)/(4 - 3) = (2 + √3)/1 =
= 2 + √3
c)
7/(4 - √2) = 7(4 + √2)/[(4 - √2)(4 + √2)] = 7(4 + √2)/(16 - 2) = 7(4 + √2)/14 =
= (4 + √2)/2
d)
(3 - √3)/(2√5 - 1) = [(3 - √3)(2√5 + 1)]/[(2√5 - 1)(2√5 + 1)] =
= [(3 - √3)(2√5 + 1)]/(4 * 5 - 1) = [(3 - √3)(2√5 + 1)]/(20 - 1) =
= [(3 - √3)(2√5 + 1)]/19
3.
(3a - 2)² - 2(a + 2)(a - 2) = 9a² - 12a + 4 - 2(a² - 4) =
= 9a² - 12a + 4 - 2a² + 8 = 7a² - 12a + 12
Dla a = - √3
7a² - 12a + 12 = 7 * (- √3)² - 12 * (- √3) + 12 = 7 * 3 + 12√3 + 12 =
= 21 + 12√3 + 12 = 33 + 12√3 = 3(11 + 4√3)
4.
x⁴ - [(x - 1)² + (x - 1)(x + 1)]² = x⁴ - [(x² - 2x + 1 + x² - 1]² =
= x⁴ - (2x² - 2x)² = x⁴ - (4x⁴ - 8x³ + 4x⁴) = x⁴ - 4x⁴ + 8x³ - 4x⁴ =
= - 7x⁴ + 8x³
5.
(√2 + √8)² = (√2)² + 2√(2 * 8) + (√8)² = 2 + 2√16 + 8 = 10 + 2 * 4 =
= 10 + 8 = 18
(√3 + 2√6)² = (√3)² + 2 * 2√18 + (2√6)² = 3 + 4√(9 * 2) + 4 * 6 =
= 3 + 4 * 3√2 + 24 = 27 + 12√2 = 3(9 + 4√2)
(√10 - √3)(√10 + √3) = (√10)² - (√3)² = 10 - 3 = 7
6.
(5 + √3x)² = 25 + 10√3x + 3x² = 3x² + 10√3x + 25
(1/6x - 2)² = 1/36x² - 4/6x + 4 = 1/36x² - 2/3x + 4
(0,2x - √7)(0,2x + √7) = (0,2x)² - (√7)² = 0,04x² - 7
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Odpowiedź:
1.
(√2x + 5)² > 2x² + 5
2x² + 10√2x + 25 > 2x² + 5
2x² - 2x² + 10√2x > 5 - 25
10√2x > - 20
x > - 20/10√2
x > - 20√2/(10 * 2)
x > - 20√2/20
x > - √2
2.
a)
1/√7 = 1/√7 * √7/√7 = √7/√7² = √7/7
b)
1/(2 - √3) = (2 + √3)/[(2 - √3)(2 + √3)] = (2 + √3)/(4 - 3) = (2 + √3)/1 =
= 2 + √3
c)
7/(4 - √2) = 7(4 + √2)/[(4 - √2)(4 + √2)] = 7(4 + √2)/(16 - 2) = 7(4 + √2)/14 =
= (4 + √2)/2
d)
(3 - √3)/(2√5 - 1) = [(3 - √3)(2√5 + 1)]/[(2√5 - 1)(2√5 + 1)] =
= [(3 - √3)(2√5 + 1)]/(4 * 5 - 1) = [(3 - √3)(2√5 + 1)]/(20 - 1) =
= [(3 - √3)(2√5 + 1)]/19
3.
(3a - 2)² - 2(a + 2)(a - 2) = 9a² - 12a + 4 - 2(a² - 4) =
= 9a² - 12a + 4 - 2a² + 8 = 7a² - 12a + 12
Dla a = - √3
7a² - 12a + 12 = 7 * (- √3)² - 12 * (- √3) + 12 = 7 * 3 + 12√3 + 12 =
= 21 + 12√3 + 12 = 33 + 12√3 = 3(11 + 4√3)
4.
x⁴ - [(x - 1)² + (x - 1)(x + 1)]² = x⁴ - [(x² - 2x + 1 + x² - 1]² =
= x⁴ - (2x² - 2x)² = x⁴ - (4x⁴ - 8x³ + 4x⁴) = x⁴ - 4x⁴ + 8x³ - 4x⁴ =
= - 7x⁴ + 8x³
5.
a)
(√2 + √8)² = (√2)² + 2√(2 * 8) + (√8)² = 2 + 2√16 + 8 = 10 + 2 * 4 =
= 10 + 8 = 18
b)
(√3 + 2√6)² = (√3)² + 2 * 2√18 + (2√6)² = 3 + 4√(9 * 2) + 4 * 6 =
= 3 + 4 * 3√2 + 24 = 27 + 12√2 = 3(9 + 4√2)
c)
(√10 - √3)(√10 + √3) = (√10)² - (√3)² = 10 - 3 = 7
6.
a)
(5 + √3x)² = 25 + 10√3x + 3x² = 3x² + 10√3x + 25
b)
(1/6x - 2)² = 1/36x² - 4/6x + 4 = 1/36x² - 2/3x + 4
c)
(0,2x - √7)(0,2x + √7) = (0,2x)² - (√7)² = 0,04x² - 7